Process heat transfer. Volume 1, principles, applications and rules of thumb. - Choudhury, Asim Kumar Roy (Woodhead publishing in textiles, 2014)
Colour and appearance perceptions are very complex psychological phenomena. Written by one of the foremost authorities in the field, this major two-volume work addresses the key topics required to understand the issues and manage colour effectively. Principles of colour appearance and measurement Volume 1 addresses how objects appear to viewers, how they perceive colour and the major types of instrumentation used to measure colour. Chapters detail the characteristics of light sources and object colour and appearance attributes. The complexities of human visual perception, unusual visual.